DIGITAL CITIZENSHIP SEBAGAI INSTRUMEN KONTROL SOSIAL: ANALISA PARTISIPASI WARGA NEGARA DIGITAL DI PLATFORM CHANGE.ORG - Silitonga, Novance (Oratio Directa: Jurnal Komunikasi, Media Massa dan Budaya, 2025)
ABSTRACT Digital citizenship provides a vast space for participation. Without geographical constraints, individuals do not require physical mobility to express their voices. Digital citizens possess significant power as instruments of social control over events occurring within their surroundings. This study indicates several key findings. Not all online petitions automatically lead to policy change; many function primarily to influence agenda-setting or to increase public attention. The success of petitions typically depends on the support of complementary advocacy strategies, such as media engagement, campaigns, and civil society organizations, rather than relying solely on the accumulation of signatures. In Indonesia, the use of online petitions to drive policy change remains relatively recent and is not yet formally regulated within the legal framework. The absence of verification processes for facts and events presented on social media may lead digital citizens into forming misleading and irresponsible judgments. High accessibility and broad participation, when not accompanied by digital ethics, can result in forms of social sanctioning that lack accountability. Rather than serving as effective instruments of public policy control, digital citizens risk becoming entangled in manipulative practices of news and information dissemination when mechanisms for data verification are absent. Keywords: Online Petitions, Hashtag Campaigns, Policy Criticism through Social Media.